Irritable urethral syndrome: follow up study in general practice. Issue 6512 (4th January 1986) - O'Dowd, T C; Pill, R; Smail, J E; Davis, R H
Abstract : Two years after a microbiological study of the urethral syndrome 25 of 31 women had had further symptoms, but only two had sought medical help for their symptoms in the year after the study. Analysis of patients' records showed that women with the urethral syndrome had higher consultation and sterilisation rates and more psychosomatic symptoms and relationship problems than matched control patients. Using the Nottingham health profile women with the urethral syndrome were more likely to mention that health problems affected their sex lives and were more likely to see themselves as having health problems than control patients. Women who have the urethral syndrome are considerable drain on the doctor's time, and management needs to be directed towards the anxious patient who makes such demands. Seeing the condition as the "irritable urethral syndrome" may help both doctor and patient to recognize the psychosomatic aspect of the problem.